2012
DOI: 10.1002/j.1532-2149.2012.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Growing pains: Twin family study evidence for genetic susceptibility and a genetic relationship with restless legs syndrome

Abstract: This first twin family study of GP provides evidence for a genetic aetiology and for a genetic relationship to RLS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 32 publications
1
31
0
3
Order By: Relevance
“…46 The criteria are modified from Evans 38 as well as Evans and Scutter 32,47 and Champion and colleagues. 48 The features described in the diagnostic criteria for growing pains are similar to those of RLS with 2 exceptions. 46 One exception is that growing pains are strictly bilateral, whereas RLS can be unilateral or bilateral.…”
Section: Possible Rlsmentioning
confidence: 94%
See 1 more Smart Citation
“…46 The criteria are modified from Evans 38 as well as Evans and Scutter 32,47 and Champion and colleagues. 48 The features described in the diagnostic criteria for growing pains are similar to those of RLS with 2 exceptions. 46 One exception is that growing pains are strictly bilateral, whereas RLS can be unilateral or bilateral.…”
Section: Possible Rlsmentioning
confidence: 94%
“…3,7,25,52 A recent twin family study also suggested the genetic overlap between the 2 disorders. 48 The conflicting findings from various studies are partly due to different criteria for growing pains used by various investigators. Standardized and unified diagnostic criteria for growing pains are needed to accurately define the relationship between growing pains and RLS.…”
Section: Possible Rlsmentioning
confidence: 98%
“…The zygosity of the twin pairs was assessed after applying the 12-question formula concerning the general similarity between twins, as it was introduced by Jackson et al [29,30]. …”
Section: Methodsmentioning
confidence: 99%
“…Other theories include the local overuse syndrome theory which remains untested [8], the non-inflammatory pain syndrome theory [9], which is supported by reports for increased activity levels of children in more than 40% of the publications [2], and the hypothesis of early childhood’s pain amplification syndrome [10]. Furthermore, a twin family survey [11] provided evidence that GPs appear to bear genetic susceptibility and present genetic association with restless leg syndrome. However, as there is no reliable and valid assessment tool testing hypermobility in children, the last hypothesis remains unproven [2].…”
Section: Introductionmentioning
confidence: 99%
“…A family history of RLS has been reported in 60% of idiopathic RLS patients (Champion et al, 2012;Montplaisir et al, 1997;Winkelmann et al, 2000), and several candidate polymorphisms for sleep disorders have been proposed. Published linkage analyses in families have identified seven genetic loci associated with RLS: RLS1 on chromosome 12q12-q21, RLS2 on 14q13-21, RLS3 on 9p24-p22, RLS4 on 2q33, RLS5 on 20p13, RLS6 on 19p13, and RLS7 on 16p12.1 (Bonati et al, 2003;Chen et al, 2004;Desautels et al, 2001;Kemlink et al, 2008;Levchenko et al, 2006Levchenko et al, , 2009Pichler et al, 2006).…”
Section: Introductionmentioning
confidence: 99%